The effect of biopreparations in pot experiment - Jakab, Anita; Kátai, János (Acta Agraria Debreceniensis, 2013)
In pot experiment the effect of Amykor and Organic Green Gold bioproducts and their combinations with NPK fertilizer on some soil properties (chemical parameters) and on the biomass of testplant were studied. The experiment was set up in 2012 at the Institute of Agricultural Chemistry and Soil Science, in a three replications, in a random block design. The studied soil typein the pot experiment was humus sandy soil from Debrecen-Pallag with onion (Allium cepa) test plant. At the end of the experiment (after 4 week) in our laboratory the samples of soil and plant were determined. The nitrate-nitrogen, AL-soluble phosphorus and potassium content of soil, the weight of green onion leaves, the wet weight of bulb and root of onion and biomass of onion. The results of the study were the following: – The treatments influenced positively the nitrate-nitrogen, the AL-soluble phosphorus and potassium content of soil. – The most effective treatments were the artificial fertilization (NO3-N) and the NPK+ simple dose of Amykor (AL-P2O5 and Al-K2O). – The NPK fertilization and the NPK+OGG (sprinkle in every 10 days) combinations had significant positive effect on the weight of green onion leaves. – The biofertilization and the straw+biofertilizer combinations stimulated the AL-soluble potassium content of soil occasionally. – The OGG treatment (sprinkle in every 10 days) had significant effective impact on the wet weight of bulb and root of onion. – The biomass of onion was increased by the artificial fertilization and OGG (sprinkle in every 10 days) treatment.